Controlled Single-Phase Full-Wave Rectifier Experiment for DC Shunt Motor Control - Anggara Trisna Nugraha; Rama Arya Sobhita (Journal of Marine Electrical and Electronic Technology, 2023)
A DC shunt motor is a type of direct current motor that allows for speed regulation, making it essential for applications requiring steady-state speed control and transient response optimization, particularly under load conditions. Accurate speed control is crucial in industrial automation, robotics, and precision engineering systems that demand fast response and stability. This study aims to analyze the relationship between motor speed and reference speed, as well as its correlation with voltage and current variations. The research is conducted using PSIM software, a widely used simulation tool in power electronics and motor control studies. The methodology involves designing a controlled single-phase full-wave rectifier circuit within PSIM, incorporating gating block angle variations to observe their effects on motor performance. The data obtained are analyzed using descriptive analytical methods to assess system behavior. The experimental results indicate that motor speed increases as the firing angle decreases, and conversely, the speed reduces when the firing angle is increased, particularly under zero torque conditions (0 Nm). When a load torque of 5 Nm is applied, the relationship becomes inversely proportional, demonstrating a dependency between torque, voltage control, and motor speed stability. These findings provide valuable insights into DC shunt motor control optimization, highlighting the effectiveness of phase-controlled rectification in improving motor performance under variable load conditions.